Optimizing Staff Mentoring in Character Formation of Students in the Discipleship Program at YWAM Sentani Papua - Ming, David; Sandeep, Godikay; Dully, Stefanus (Jurnal Pendidikan Agama Kristen (JUPAK), 2025)
Character education is an important aspect in forming a young generation that is not only academically superior, but also has integrity and strong moral values. YWAM (Youth With A Mission) Sentani Papua is one of the educational institutions that integrates academic and spiritual learning through a discipleship program. However, the success of this program is highly dependent on the quality of staff mentoring for students. This study aims to examine how staff mentoring can be optimized in the formation of student character, as well as identify the challenges faced and strategies for increasing the capacity of mentors. The data shows that most staff do not have specific training in character education, which has an impact on the effectiveness of discipleship. Therefore, ongoing training and parental involvement are needed to support the holistic character formation process. Routine evaluation of program implementation is also needed so that it can be continuously improved. This study is expected to contribute to the development of character education in a faith-based educational environment